Gen Z dan Kosmetik Lokal Halal - Tia Septianda; Anita Priantina (Airlangga Journal of Innovation Management, 2024)
This research aims to determine the influence of the halal label, knowledge and religiosity on local cosmetics labeled halal. Looking at the surrounding environment, many generation Z people still don't care about choosing local cosmetics that are labeled halal. Apart from that, this research advises consumers or cosmetic users to be careful in choosing the cosmetic brands they use, especially local cosmetics. Therefore, the author decided to conduct research on generation Z, both men and women who live in Jabodetabek. Around 112 respondents completed the survey, and data collection was done using questionnaire. The data were analyzed using software SmartPLS 3.0 with analysis method structural equation modeling (SEM). Result showed that consumers' decisions to buy are significantly and favourably influenced by the halal label. This shows that consumers are increasingly aware of the importance of choosing locally produced cosmetics that are halal certified. Further evidence of a noteworthy degree of awareness of the significance of selecting halal-labelled products comes from the significant link that exists between customers' knowledge of local cosmetics and their shopping decisions. This study suggests further exploration of the specific factors that drive the positive influence of the halal label and emphasizes the need for a deeper understanding of the complex dynamics between religiosity and purchasing decisions, thereby contributing valuable insights for industry stakeholders.